2018
DOI: 10.1017/asr.2017.144
|View full text |Cite
|
Sign up to set email alerts
|

From Pre-Colonial Past to the Post-Colonial Present: The Contemporary Clan-Based Configurations of Statebuilding in Somalia

Abstract: Abstract:This article is driven by an empirical paradox over where Somalia came from (pre-colonial clan-states) and where it ended up (return to pre-colonial clano-territorial conflicts). Existing academic studies on contemporary Somalia, which were supposed to provide critical analysis, continue to applaud the creation of clan-states within the failed state of Somalia. Based on a variety of unique primary sources, this article offers a new perspective on the current state formation processes occurring in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The international intervention in Somalia has systematically failed to create a Weberian central state in Mogadishu (Hagmann, 2016; Ingiriis, 2018). Instead, order in the city emerges from a ‘political marketplace’ (Ingiriis, 2020), a modern system of governance characterized by a monetized transactional politics, in which loyalties are bought and sold by ‘political entrepreneurs’ engaged in pervasive rent-seeking and monetized patronage (De Waal, 2015).…”
Section: Transgressing the Boundariesmentioning
confidence: 99%
“…The international intervention in Somalia has systematically failed to create a Weberian central state in Mogadishu (Hagmann, 2016; Ingiriis, 2018). Instead, order in the city emerges from a ‘political marketplace’ (Ingiriis, 2020), a modern system of governance characterized by a monetized transactional politics, in which loyalties are bought and sold by ‘political entrepreneurs’ engaged in pervasive rent-seeking and monetized patronage (De Waal, 2015).…”
Section: Transgressing the Boundariesmentioning
confidence: 99%
“…Somali women's movements started in the 1940s as the country pushed for independence. During colonialism, women were an important element of various grassroots organizations and social movements, including the (“women's movement”), the Somali Youth League (SYL), and Sayyid Mohamed Abdullah Hassan's Dervish Movement (Ingiriis, 2018). Somali women under the British Military Administration joined the nationalist struggle with equal fervour in the 1940s.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With reference to Somalia, Mohamed Haji Ingiriis argues that 'contemporary Somalis are reverting to a pre-colonial realm where each clan had its clan sultan seeking for a clan-state of its own right'. 12 Clannishness has been called 'the categorical imperative of Somali political practice' 13 and is often described as the proverbial iceberg that sank Somalia's postcolonial state-building venture. 14 Anthropologists have critiqued the segmentary lineage paradigm as 'primordialist' and observed that genealogy functions in Somalia and elsewhere as a tool of political manipulation.…”
Section: The Outbreak Of the Civil War In Northern Ethiopia In 2020 B...mentioning
confidence: 99%